Pengaruh Penggunaan Multimedia Berbasis Aplikasi Cyberlink Power Director Terhadap Hasil Belajar Siswa Kelas VII SMP Islam Plus Baitussalam - Pitria, Dina; Mahpudin, Asep (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Learning at SMP Islam Plus Baitussalam still uses textbooks learning medium and the lecture method, where only the teacher provides explanations, making the learning process monotonous. The objective of this research is to improve student learning outcomes by implementing multimedia based on Power Director. The research method used in this study is a quantitative method with a Quasi Experimental type and a Pretest-Posttest Control Design. The population used in this study consists of students from class VII-Uwais Al-Qarni and VII-Fatimah, totaling 44 students. Data collection techniques through observation, test techniques, and questionnaires. The data analysis techniques in this study are normality test, homogeneity test, and hypothesis test (T-Test). The research results show a difference in learning outcomes between students taught using conventional methods and those using PowerDirector multimedia learning on the topic of Indonesia's natural resource potential. Based on the hypothesis test, the average increase in learning scores for the experimental group is 76.00, while the control group is 67.33. The increase in the learning outcome scores of the experimental group was 8.67 higher compared to the control group. The t-test results show that indicating a significant difference in the improvement of learning outcomes between the experimental group and the control group. Thus, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted.